Investigating Abiotic and Biotic Mechanisms of Pyrite Reduction - Spietz, Rachel L.; Payne, Devon; Kulkarni, Gargi; Metcalf, William W.; Roden, Eric E.; Boyd, Eric S. (Frontiers in Microbiology, 2022)
Pyrite (FeS2) has a very low solubility and therefore has historically been considered a sink for iron (Fe) and sulfur (S) and unavailable to biology in the absence of oxygen and oxidative weathering. Anaerobic methanogens were recently shown to reduce FeS2 and assimilate Fe and S reduction products to meet nutrient demands. However, the mechanism of FeS2 mineral reduction and the forms of Fe and S assimilated by methanogens remained unclear. Thermodynamic calculations described herein indicate that H2 at aqueous concentrations as low as 10-10M favors the reduction of FeS2, with sulfide (HS-) and pyrrhotite (Fe1-xS) as products; abiotic laboratory experiments confirmed the reduction of FeS2 with dissolved H2 concentrations greater than 1.98x10-4M H2. Growth studies of Methanosarcina barkeri provided with FeS2 as the sole source of Fe and S resulted in H2 production but at concentrations too low to drive abiotic FeS2 reduction, based on abiotic experimental data. A strain of M. barkeri with deletions in all [NiFe]-hydrogenases maintained the ability to reduce FeS2 during growth, providing further evidence that extracellular electron transport (EET) to FeS2 does not involve H2 or [NiFe]-hydrogenases. Physical contact between cells and FeS2 was required for mineral reduction but was not required to obtain Fe and S dissolution products. The addition of a synthetic electron shuttle, anthraquinone-2,6-disulfonate, allowed for biological reduction of FeS2 when physical contact between cells and FeS2 was prohibited, indicating that exogenous electron shuttles can mediate FeS2 reduction. Transcriptomics experiments revealed upregulation of cytoplasmic oxidoreductases during M. barkeri growth on FeS2, which may indicate involvement in provisioning low potential electrons for EET to FeS2. Collectively, data presented herein indicates that reduction of insoluble FeS2 by M. barkeri occurs via EET from the cell to mineral surface resulting in the generation of aqueous HS- and mineral-associated Fe1-xS. Solubilized Fe(II), but not HS-, from Fe1-xS reacts with aqueous HS- yielding aqueous iron sulfur clusters (FeSaq) that serve as the Fe and S source for methanogen growth. FeSaq nucleation and subsequent precipitation on the cell surface may result in accelerated EET to FeS2, resulting in positive feedback between cell activity and FeS2 reduction.